2016
DOI: 10.1098/rstb.2015.0186
|View full text |Cite
|
Sign up to set email alerts
|

The coevolution of innovation and technical intelligence in primates

Abstract: One contribution of 15 to a theme issue 'Innovation in animals and humans: understanding the origins and development of novel and creative behaviour'.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
98
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(102 citation statements)
references
References 70 publications
4
98
0
Order By: Relevance
“…Across primates, support for multiple, nonexclusive hypotheses for enlarged brain (particularly neocortex) size has been identified in comparative studies, emphasizing the roles of social complexity (e.g., group size) (28,29), ecological intelligence (e.g., dietary complexity) (30,31), technical intelligence (e.g., tool use and technical innovation) (21,25,32), and behavioral complexity (e.g., innovativeness, social learning, and tactical deception) (21,25,33). Further, several comparative studies have found that larger brained primates have slower life histories, including longer juvenile periods and overall lifespans (e.g., ref.…”
mentioning
confidence: 99%
“…Across primates, support for multiple, nonexclusive hypotheses for enlarged brain (particularly neocortex) size has been identified in comparative studies, emphasizing the roles of social complexity (e.g., group size) (28,29), ecological intelligence (e.g., dietary complexity) (30,31), technical intelligence (e.g., tool use and technical innovation) (21,25,32), and behavioral complexity (e.g., innovativeness, social learning, and tactical deception) (21,25,33). Further, several comparative studies have found that larger brained primates have slower life histories, including longer juvenile periods and overall lifespans (e.g., ref.…”
mentioning
confidence: 99%
“…In the present analysis, Sol et al [88] test the prediction that innovation propensity is a co-opted product of a collection of traits that allow an organism to cope with environmental change rather than a direct target of selection. As also seen in Navarrete et al's contribution [96], there is a welcome effort to transition from correlational analyses to identifying the most likely causal scenarios. Relative brain size exerts a common causal effect on innovation propensity and lifespan, which like Navarrete et al's [96] present finding of a direct relationship between technical innovations and brain size, point to a causal rather than to correlational relationship between brain size and innovativeness.…”
Section: Is Innovation Selected Upon Directly or Is Itmentioning
confidence: 99%
“…As also seen in Navarrete et al's contribution [96], there is a welcome effort to transition from correlational analyses to identifying the most likely causal scenarios. Relative brain size exerts a common causal effect on innovation propensity and lifespan, which like Navarrete et al's [96] present finding of a direct relationship between technical innovations and brain size, point to a causal rather than to correlational relationship between brain size and innovativeness. Sol et al [88] go on to replicate previous work showing that both habitat and diet generalism are also predictors of higher innovation rates [94,97].…”
Section: Is Innovation Selected Upon Directly or Is Itmentioning
confidence: 99%
“…Cultural innovations in humans and in other animals include the ability to use (tools) or modify the environment [56], specific (social or asocial) behaviours [57] and adornment that influences mating success [58]. Moreover, several studies have investigated the tendency to innovate itself as a trait (with little supporting evidence, [59,60]), or as a correlate of either life-history traits such as maximum lifespan in birds [61], or cognitive traits such as brain size in birds and primates [62,63]. These and other general phenomena hint at an important feature of innovations: they usually involve multiple levels of organization [16,30,64,65].…”
Section: The Scope Of Innovation and The Innovation Ecosystemmentioning
confidence: 99%